1991
DOI: 10.1515/jpme.1991.19.1-2.73
|View full text |Cite
|
Sign up to set email alerts
|

Duration, amplitude and shape of accelerations in relation to fetal body movements in behavioral state 2F

Abstract: The relationship between fetal movements and fetal heart rate accelerations was analyzed in 34 healthy near term fetuses. Periods of coincidence 2F (C2F) with a mean duration of 34 +/- 6 minutes per fetus were selected, with a total of 463 accelerations. Nineteen percent of single body movements and 71% of compilations of movements were accompanied by an acceleration. The minimal duration of single movements associated with accelerations was 4-5 seconds. Movements with associated accelerations differed signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…Systems for interpretation of antenatal CTG have been used in clinical practice (Beksac et al 1990; Dawes et al 1991) for the identification of features, such as basal FHR, heart rate variability and accelerations. Although some correlation between these features and other changes in fetal physiology has been shown (Van Woerden et al 1990; Dawes et al 1992) a predictive capability for perinatal outcome could not be demonstrated. The antenatal system designed by Wickham et al (1983) has been modified and used in early labour (Pello et al 1991), but they found no clear association between the measurement of FHR variation and umbilical artery base excess on delivery.…”
mentioning
confidence: 99%
“…Systems for interpretation of antenatal CTG have been used in clinical practice (Beksac et al 1990; Dawes et al 1991) for the identification of features, such as basal FHR, heart rate variability and accelerations. Although some correlation between these features and other changes in fetal physiology has been shown (Van Woerden et al 1990; Dawes et al 1992) a predictive capability for perinatal outcome could not be demonstrated. The antenatal system designed by Wickham et al (1983) has been modified and used in early labour (Pello et al 1991), but they found no clear association between the measurement of FHR variation and umbilical artery base excess on delivery.…”
mentioning
confidence: 99%
“…In contrast, FHR usually shows decelerations in response to contraction and this is more so during the second stage of labor. Furthermore, if FHR show accelerations (usually in association with fetal movement) they tend to be irregular, of short duration, limited elevations, not lasting the entire contraction [20] and usually are sporadic never showing repeated accelerations [17,18]. • Tracings of the first stage of labor showing low baseline and early-type decelerations could be produced by MHR [18,21,22].…”
Section: Discussionmentioning
confidence: 99%
“…In general, complex movements are associated with a greater increase in heart rate than are isolated limb movements. 17 Nevertheless, this association is far from complete because the administration of gallamine to fetal sheep abolishes movement but heart rate accelerations continue to be present. 18 -19 Although somatic-cardiac coupling may possibly explain the difference in heart rate response that we observed between slow and fast motor habituators, we would expect to see, if this were the case, some trend toward habituation of FHR as the amount of fetal movement decreased with repeated stimulation.…”
Section: Discussionmentioning
confidence: 99%